Queering borders: Language, sexuality and migration - Murray, David A.B. (Journal of Language and Sexuality, 2014)
Preface to the special issue on queering borders in the journal of language and sexuality.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; canada; cours; discipline; histoire et politique; identités LGBTQIA2+; migration; migrations queer; premier cycle; queer; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Gender & difference in a globalizing world twenty-first century anthropology - Mascia-Lees, Frances E. (Waveland Press, 2010)
"Mascia-Lees'... ability to synthesize ideas rewards readers wih a text that clearly conceptualizes how differences of gender, race, class, and sexuality structure today's complex globalizing world. It exposes the strengths and weaknesses of different theoretical orientations used in anthropology to study gender, difference, power, and inequality including feminist anthropology; black feminist anthropology; lesbian/gay/bisexual/transgendered theory; practice, postcolonial, symbolic, and psychological anthropology; as well as social evolutionism, sociobiology, and evolutionary pscyhology, among others"
Keywords: afro-féminisme; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; histoire et politique; intersectionnalité; premier cycle; queer; sciences humaines; sex1911; sex2283; thématiques; travail